Justifying Alexander Pope's Unjustifiable Rhymes. (29th October 2019) - Tomalin, Marcus
Abstract: Drawing upon recent research into historical phonology, this article re-examines the prosodic structure of Alexander Pope's verse. The underlying purpose is to demonstrate that the widespread tendency to hear Pope's poetry with a modern ear can lead to literary-critical interpretations that are alarmingly brittle. By contrast, a willingness to undertake some kind of pronunciation-related auditory archaeology can reveal phonological patterns that would otherwise remain hidden—and an awareness of these patterns can transform our appreciation of his intricate couplet art. A task of this kind necessarily involves a careful reading of prominent contemporaneous dictionaries, grammar textbooks, and orthoepic works, as well as recent revisionist studies of eighteenth-century English phonology. As an initial case study, the central discussion in this article will focus predominantly on two words: and . Jonathan Swift accused Pope of deploying too many 'unjustifiable rhymes' for these words in his Iliad, and seeking to understand this critique leads to an exploration of how Pope structured his poetry using subtle phonological correspondences which frequently occur at locations other than the tenth syllable in his couplets.